2015
DOI: 10.1002/ange.201506663
|View full text |Cite
|
Sign up to set email alerts
|

Poly(N‐isopropylacrylamid)‐Phasendiagramme: 50 Jahre Forschung

Abstract: Im Jahr 1968 publizierten Heskins und Guillet die erste systematische Studie über das Phasendiagramm von Poly(N‐isopropylacrylamid) (PNIPAM), einem zu jener Zeit “jungen Polymer”, das erstmalig 1956 synthetisiert worden war. Seitdem ist PNIPAM zu einem führenden Vertreter der wachsenden Familie temperatur‐ und reizempfindlicher Polymere geworden. Seine thermische Antwort ist fraglos durch sein Phasenverhalten begründet. Nach nunmehr 50 Jahren Forschung zeichnet sich noch immer kein einheitliches, quantitatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 104 publications
(346 reference statements)
0
8
0
Order By: Relevance
“…The mechanism of termination reaction for PNIPAM through free radical polymerization has been investigated in the literature [52,53]. The literature kinetics data regarding the PNIPAM termination mechanism take into account three possibilities, with different contributions depending on the reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of termination reaction for PNIPAM through free radical polymerization has been investigated in the literature [52,53]. The literature kinetics data regarding the PNIPAM termination mechanism take into account three possibilities, with different contributions depending on the reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Poly­( N -isopropylacrylamide) (PNIPAM) is the most commonly used stimuli-sensitive smart polymer, characterized by its well-defined lower critical solution temperature (LCST) of approximately 32 °C in water. Radical polymerization of aqueous N -isopropylacrylamide (NIPAM) solution above the LCST yields soft colloidal particles in the size range of tens of nanometers to a few microns .…”
Section: Introductionmentioning
confidence: 99%
“…The LCST of pNIPAM (and VPTT of pNIPAM gels) is known to be sensitive to end groups or, in the case of block copolymers, the other blocks. 86 For example, Xia et al demonstrated that that an N-phenyl amide end group lowered the cloud point of pNIPAM by as much as 9 °C compared to the unsubstituted amide. 87 Additionally, the tacticity of pNIPAM is also known to affect its LCST and the tacticity can be affected by the synthesis conditions, e.g the solvent.…”
Section: Synthesis and Properties Of Paa-b-pnipam Block Copolymersmentioning
confidence: 99%